PENUMBUHAN KECERDASAN SPIRITUAL MELALUI NGAJI TAFSIR AL-QUR’AN DI MI AL-JABBAR SUMBERAGUNG BOJONEGORO - Fadhilatun Ni’mah; Mukhoiyaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Spiritual intelligence can help other intelligence. This study investigates how reciting tafsir Al-Qur'an at MI Al-Jabbar Bojonegoro can increase spiritual intelligence. This study applies a descriptive qualitative approach. Data was collected through interviews and observations to determine the increase in spiritual intelligence through reciting tafsir. The research results show that reciting tafsir can increase spiritual intelligence. This activity helps students understand how to interpret verses and use them as examples in everyday life. MI Al-Jabbar is an educational environment that supports religious practices and encourages reading and interpretation of the Al-Qur'an to increase spiritual intelligence. This study shows the importance of studying the interpretation of the Koran in increasing a person's spiritual intelligence and the importance of educational institutions in cultivating individual spiritual intelligence, especially in basic education. So in conclusion, reciting tafsir is a good method for cultivating spiritual intelligence and supporting someone to become wiser in facing increasingly sophisticated times.